Ductal Carcinoma In Situ and Margins <2 mm: Contemporary Outcomes With Breast Conservation. Issue 1 (January 2019) - Tadros, Audree B.; Smith, Benjamin D.; Shen, Yu; Lin, Heather; Krishnamurthy, Savitri; Lucci, Anthony; Barcenas, Carlos H.; Hwang, Rosa F.; Rauch, Gaiane; Santiago, Lumarie; Strom, Eric A.; DeSnyder, Sarah M.; et al.
Abstract : Objective: To determine the relationship between negative margin width and locoregional recurrence (LRR) in a contemporary cohort of ductal carcinoma in situ (DCIS) patients. Background: Recent national consensus guidelines recommend an optimal margin width of 2 mm or greater for the management of DCIS; however, controversy regarding re-excision remains when managing negative margins <2 mm. Methods: One thousand four hundred ninety-one patients with DCIS who underwent breast-conserving surgery from 1996 to 2010 were identified from a prospectively managed cancer center database and analyzed using univariate and multivariate Cox proportional hazard models to determine the relationship between negative margin width and LRR with or without adjuvant radiation therapy (RT). Results: A univariate analysis revealed that age <40 years (n = 89; P = 0.02), no RT (n = 298; P = 0.01), and negative margin width <2 mm (n = 120; P = 0.005) were associated with LRR. The association between margin width and LRR differed by adjuvant RT status (interaction P = 0.02). There was no statistical significant difference in LRR between patients with <2 mm and ≥2 mm negative margins who underwent RT (10-yr LRR rate, 4.8% vs 3.3%, respectively; hazard ratio, 0.8; 95% CI, 0.2–3.2; P = 0.72). For patients who did not undergo RT, those with margins <2 mm were significantly more likely to develop a LRR than were those with margins ≥2 mm (10-yr LRR rate, 30.9% vs 5.4%, respectively; hazard ratio, 5.5; 95% CI, 1.8–16.8, P = 0.003). Conclusions: Routine additional surgery may not be justified for patients with negative margins <2 mm who undergo RT but should be performed in patients who forego RT.